Outdoor, indoor, and personal black carbon exposure from cookstoves burning solid fuels. (6th November 2015) - Downward, G. S.; Hu, W.; Rothman, N.; Reiss, B.; Wu, G.; Wei, F.; Xu, J.; Seow, W. J.; Brunekreef, B.; Chapman, R. S.; Qing, L.; Vermeulen, R.
Abstract: Black carbon (BC) emissions from solid fuel combustion are associated with increased morbidity and mortality and are important drivers of climate change. We studied BC measurements, approximated by particulate matter (PM2.5 ) absorbance, in rural Yunnan province, China, whose residents use a variety of solid fuels for cooking and heating including bituminous and anthracite coal, and wood. Measurements were taken over two consecutive 24‐h periods from 163 households in 30 villages. PM2.5 absorbance (PMabs ) was measured using an EEL 043 Smoke Stain Reflectometer. PMabs measurements were higher in wood burning households (16.3 × 10 −5 /m) than bituminous and anthracite coal households (12 and 5.1 × 10 −5 /m, respectively). Among bituminous coal users, measurements varied by a factor of two depending on the coal source. Portable stoves (which are lit outdoors and brought indoors for use) were associated with reduced PMabs levels, but no other impact of stove design was observed. Outdoor measurements were positively correlated with and approximately half the level of indoor measurements ( r  = 0.49, P  < 0.01). Measurements of BC (as approximated by PMabs ) in this population are modulated by fuel type and source. This provides valuable insight into potential morbidity, mortality, and climate change contributions of domestic usage of solid fuels.